2019
DOI: 10.1299/mej.18-00294
|View full text |Cite
|
Sign up to set email alerts
|

Solidification characteristics of green tea as raw material of solid fuel

Abstract: Biocoke (BIC), made from all types of biomass is a solid fuel. Hemicellulose and lignin, essential chemical components of biomass, work as bonding agents of BIC solidification because they have softening and fluidity characteristics. Their characteristics make bonding structure inside of BIC during the formation process. Previous studies suggested that physical and mechanical characteristics of BIC are different if raw materials (kinds of biomass) are different even if forming conditions are the same. It was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Experimental results suggested that samples with high hemicellulose and lignin contents, together with high moisture contents underwent fluidization at lower temperatures. This is consistent with the fact that biomass containing large amounts of hemicellulose, such as herby biomass (Tagami and Ida, 2019), undergoes fluidization at lower temperatures. Furthermore, we previously assessed the compressive strength of Bio-coke produced from five biomass sources, and found that higher cellulose content, resulted in higher compressive strength (Tagami and Ida, 2018).…”
Section: Introductionsupporting
confidence: 85%
“…Experimental results suggested that samples with high hemicellulose and lignin contents, together with high moisture contents underwent fluidization at lower temperatures. This is consistent with the fact that biomass containing large amounts of hemicellulose, such as herby biomass (Tagami and Ida, 2019), undergoes fluidization at lower temperatures. Furthermore, we previously assessed the compressive strength of Bio-coke produced from five biomass sources, and found that higher cellulose content, resulted in higher compressive strength (Tagami and Ida, 2018).…”
Section: Introductionsupporting
confidence: 85%
“…The highest and lowest apparent density of BIC in this research is at 1.435 g/cm 3 and 1.416 g/cm 3 repectively, from 15% of additional hemicellulose. This result is explained by the softening behavior of hemicellulose, the softening temperature of dried hemicellulose has been reported at 423 K by Goto et al, 2012 andTagami et al, 2019. The softening behavior of Japanese cedar was reported by Tagami et al, 2019 at approximately 460 K. Since the forming temperature of this research is 463 K, the increasing of additional hemicellulose results in greater reaction between materials particles.…”
Section: Results and Discussion 31 Apparent Density And Heating Valuesupporting
confidence: 51%
“…The forming temperature of BIC at 463 K in this study is in the softening region of Japanese cedar (for the initial moisture content at 10 wt. %) and 20 K greater than glucomannan powder (Tagami et al, 2019). As mentions earlier about the reaction during the BIC transformation process in the molecular level, the additional hemicellulose react and bond with the molecules JC components.…”
Section: Compressive Strengthmentioning
confidence: 72%
See 2 more Smart Citations